Minutes of high-level guidance not captured by the "pink Aide Memoire" - Bassi, Filippo; Sanchez-Garcia, Miguel; Baum, Michael (2023)
CWANA Genetic Innovation and Regional CGIAR Initiatives consultation meeting with NARES to develop guiding principles up to 2030 for the development of genetic innovations targeted to the region, meeting in Turkiye, 13-15 Dec 2022.